2017
DOI: 10.1002/lary.26354
|View full text |Cite
|
Sign up to set email alerts
|

Time‐driven activity‐based costing to estimate cost of care at multidisciplinary aerodigestive centers

Abstract: 2c. Laryngoscope, 127:2152-2158, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In terms of outcomes, multidisciplinary aerodigestive programs offer the opportunity to improve safety by shortening procedural times and consolidating skills. 7,14 In terms of costs, these programs can lower the opportunity costs to patients and families by combining visits and procedures. The charge to payers is also lowered because procedural elements that are associated with time under anesthetic, such as anesthesia medication and service charges as well as facility charges, are reduced when procedures are consolidated.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of outcomes, multidisciplinary aerodigestive programs offer the opportunity to improve safety by shortening procedural times and consolidating skills. 7,14 In terms of costs, these programs can lower the opportunity costs to patients and families by combining visits and procedures. The charge to payers is also lowered because procedural elements that are associated with time under anesthetic, such as anesthesia medication and service charges as well as facility charges, are reduced when procedures are consolidated.…”
Section: Discussionmentioning
confidence: 99%
“…The main cost driver in our TD-ABC approach was time (Kaplan & Anderson, 2007). This model has already been successfully applied in the healthcare field (Garcia et al, 2017;Laviana et al, 2016;Stouthuysen, Schierhout, Roodhooft, & Reusen, 2014) and has provided useful results on the cost-efficiency of various policies.…”
Section: Designing the Methodology And Researchmentioning
confidence: 99%
“…It is usually performed by physicians as part of multidisciplinary care (aerodigestive team) for a child with recalcitrant CC and dysphagia. Studies 19,20 have shown a 20%–40% cost savings for children who are managed comprehensively in a multidisciplinary setting compared to a single specialty evaluation. Therefore, appropriate referral and evaluation of persistent/recalcitrant cough by aerodigestive team (multidisciplinary team) may lead to earlier accurate diagnosis with likely cost savings.…”
Section: Role Of Triple Endoscopy In CCmentioning
confidence: 99%